2012
DOI: 10.1016/j.evalprogplan.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Neurodegenerative Conditions Coordinated Care Program (NCCCP) in Western Australia: Barriers to better service provision

Abstract: This paper details a 2009-2010 evaluation of the Neurodegenerative Conditions CoordinatedCare Program (NCCCP) commissioned by the Disability Services Commission (DSC) in Western Australia (WA). The program, run by the Multiple Sclerosis Society of WA (Inc.) provides in-home care and supports and respite for people who are under the age of sixty-five and diagnosed with a rapidly degenerative neurological condition. In 2009, the identified barriers to the better provision of services included: shortage of qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Home care for patients with ALS often decreases as the disease progresses. 8,11,13,[19][20][21] This results in a greater care burden 4,22 and affects patients' future planning. 23,24 Respite admission is therefore important for severe-stage ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Home care for patients with ALS often decreases as the disease progresses. 8,11,13,[19][20][21] This results in a greater care burden 4,22 and affects patients' future planning. 23,24 Respite admission is therefore important for severe-stage ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of long-term home health care (e.g., for wheel-chair bound MS patients) is to maintain the patient's highest level of functioning, as well as to facilitate the patient's ability to live with his/her illness and disability. In general, studies from other countries have demonstrated that while home-based services do not reduce disability in MS patients, they improve their quality of life and provide respite to family members (Dunn, 2010;Mutch, 2010;Bahn and Giles, 2012;Giordano et al, 2013). Our understanding of long-term care needs of the MS population and how these needs are met by the avail-able care options is limited.…”
Section: Discussionmentioning
confidence: 99%